Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $G$ be a group with center $Z(G)$ and let $\sim$ denote the conjugancy equivalence relation on $G$ (that is, $a \sim b$ iff $\exists g \in G$ s.t. $a = gbg^{-1}$). Finally let $[a]$ denote the conjugacy class which contains $a \in G$.

Now if $a \in Z(G)$ it is clear that $[a] = \{a\}$, for if $b = gag^{-1}$, then $b = a$ so that $[a] = \{a\}$ as desired.

Yet it is not clear to me why the converse is true (that is if $[a] = \{a\}$ that we necessarily have $a \in Z(G)$). If we assume that $[a] = \{a\}$, then clearly there exists a $g \in G$ s.t. $a = gag^{-1}$ (since $\sim$ is an equivalence relation which means $a \sim a$ $\forall a \in G$). But we cannot know that $a \in Z(G)$ until all such elements $g \in G$ satisfy this property, not merely a single one of them. How do I show this?

share|cite|improve this question
up vote 3 down vote accepted

Note that $a=gbg^{-1}$ if and only if $b=(g^{-1})a(g^{-1})^{-1}$. Hence, if $b\in[a]$, then $b\in\{hah^{-1}:h\in G\},$ and the converse holds, as well. In other words, $[a]=\{hah^{-1}:h\in G\}$. If $[a]=\{a\}$, then $hah^{-1}=a$ for all $h\in G$, so $a\in Z(G)$.

share|cite|improve this answer

The conjugacy class of an element is its orbit under conjugation by the whole group. In other words, the conjugacy class of $x$ is the set $\{g^{-1}xg : g \in G\}$. If this set only consists of $x$, then necessarily $g^{-1}xg =x$ for every $g\in G$. So $x\in Z(G)$.

share|cite|improve this answer
I'm not sure how we get from $Orb(a) = \{gag^{-1} : g \in G\}$ to $Orb(a) = [a] = \{b \in G$ : s.t. $\exists g \in G$ whereby $gbg^{-1} = a\}$. These two sets are for some reason not obviously the same to me. – user1770201 Nov 24 '12 at 10:09
@user1770201 $b=g^{-1}ag$ if and only if $a=(g^{-1})^{-1}b(g^{-1})$. – Alexander Gruber Nov 24 '12 at 16:47

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.